2017
DOI: 10.1007/s11356-017-8477-8
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the formation of formaldehyde during 2-ethylhexyl 4-(dimethylamino)benzoate demethylation in the presence of reactive oxygen and chlorine species

Abstract: In order to protect the skin from UV radiation, personal care products (PCPS) often contain chemical UV-filters. These compounds can enter the environment causing serious consequences on the water ecosystems. The aim of this study was to examine, the effect of different factors, such as UV light, the presence of NaOCl and H2O2 on the formaldehyde formation during popular UV filter, 2-ethylhexyl 4-(dimethylamino)benzoate (ODPABA) demethylation. The concentration of formaldehyde was determined by VIS spectrophot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Conceivably, the suggested products originate from a photo-retro-aldol-type reaction, initially forming N -methyl-4-nitroaniline and phenylacetaldehyde (Scheme B). The former product, known to undergo photochemical N -demethylation, , subsequently reacts and furnishes formaldehyde and p -nitroaniline (Scheme B, reaction a). Phenylacetaldehyde then undergoes oxidation to phenylacetic acid (Scheme B, reaction b) (which can suffer cleavage and form benzaldehyde and formaldehyde/formic acid (Scheme B, reaction e)) or reacts in a Norrish type 1 process and forms formaldehyde and benzaldehyde (Scheme B, reaction c).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Conceivably, the suggested products originate from a photo-retro-aldol-type reaction, initially forming N -methyl-4-nitroaniline and phenylacetaldehyde (Scheme B). The former product, known to undergo photochemical N -demethylation, , subsequently reacts and furnishes formaldehyde and p -nitroaniline (Scheme B, reaction a). Phenylacetaldehyde then undergoes oxidation to phenylacetic acid (Scheme B, reaction b) (which can suffer cleavage and form benzaldehyde and formaldehyde/formic acid (Scheme B, reaction e)) or reacts in a Norrish type 1 process and forms formaldehyde and benzaldehyde (Scheme B, reaction c).…”
Section: Results and Discussionmentioning
confidence: 99%
“…When the chlorine compounds finish oxidizing the bacteria, they combine with another chemical. This process leads to the formation of disinfection by-products (DBPs) [35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Green line indicates 5% of sludge, red line indicates 10% of sludge, and blue line indicates 20% of sludge Gago-Ferrero et al (2011), biodegradation processes of ODPABA in the sewer and during wastewater and/or sludge treatment cannot be ruled out. Moreover, our previous studies have shown that EHMC and ODPABA transform under influence of oxidising agents with formation of products significantly more toxic than the substrates themselves (Studziński et al 2017;Gackowska et al 2018). In order to verify whether biochemical transformations of UV filters occur under the influence of activated sludge, studies were carried out on model systems.…”
Section: Effect Of Activated Sludge On Removal Of Uv Filters From Wasmentioning
confidence: 99%